Translator’s Notes in a Russian Translation of Olga Tokarczuk’s Bieguni Novel - Hordy, Mirosława (Poznańskie Studia Slawistyczne, 2023)
The article addresses the issue of translator’s notes in a Russian translation of Olga Tokarczuk’s “Bieguni” novel by Irina Adelʹgejm. The main text of the original, despite its abundance in borrowings, interjections and quotations in languages other than Polish, was not provided with explanatory notes by the author. The translator, however, provided the translation with 149 notes. They are notes explaining terms, proper names, names of realities and others translated in the main text as well as notes explaining fragments formulated in the novel’s text in languages other than the language of the narration. On the basis of the undertaken analysis it is stated that the strategy of forming paratexts adopted by the translator is inconsistent. The secondary text designates an additional way of reading “Bieguni” novel, but it does not impose it as using the notes is just a possibility and depends on the reader’s choice.